Desempenho de um sistema de irrigação por gotejamento com aplicação de Água Salina - Zocoler, João Luís [UNESP]; Ribeiro, Pedro Henrique Pinto [UNESP]; Da Silva, Nelmício Furtado; Cunha, Fernando Nobre; Teixeira, Marconi Batista; Soares, Frederico Antonio Loureiro (My University, 2015)
With the increasing search for water of good quality and maximum efficiency in application, dripping irrigation has grown in areas of family farming and smallholdings. The Brazilian northeast with its poor rainwater distribution has suffered from lack of water in several regions, which has led to the use of saline water. The objective of this study was to evaluate the flow, distribution uniformity, process capability index and the statistical quality control of Shewhart of a self-compensating drip emitter with a 2.3 L h-1 flow rate using saline water. Randomized blocks with a 6 x 4 factorial design was used with six levels of saline irrigation water (0.6; 1.5; 2.5; 3.5 and 4.5 dS m-1) and four operating pressures (59, 98, 137 and 157 kPa) with three replicates. The coefficient of manufacturing variation was classified as excellent (<5%) for all levels of salinity. The salinity levels of 0.6, 1.5, 3.5 and 4.5 dS m-1 decreased flow rate according to the pressure variation.
Performance of a dripping irrigation system appying saline water
Keywords: Mean flow rate; Salinity; Uniformity